IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DALAM UPAYA PENINGKATAN MUTU PEMBELAJARAN DI MI NURUL AKBAR LEMPUING JAYA - Bakir; Feriansyah; Yuli Habibatul Imamah (UNISAN JURNAL, 2022)
The purpose of this study is to describe and analyze how the implementation of madrasa-based quality management in the process of learning effectiveness and the effectiveness of the management of teaching and educational staff at MI Nurul Akbar, Lemrub Jaya District, OKI Regency. This type of research is evaluation research using qualitative research methods. According to Sugiyono, evaluation research is research that aims to compare an event, activity and product with established standards and programs, so that evaluation research serves to explain the phenomenon. the implementation of madrasa-based management in an effort to improve the quality of learning Aqidah Akhlak lessons at MI Nurul Akbar Lemrub Jaya District OKI Regency for the 2021/2022 academic year at the planning stage is quite good. Islam.